Synthesis and Characterization of Fe3O4 and Au- co-doped Fe3O4 - Mohammed Abd Alhussein; Ahmed N. Abd (ASJ - Academic Science Journal, 2023)
Co-precipitation was used to synthesis Au/Fe3O4 nano-composites different Au contents, (XRD) , (SEM) were used to analyze the nano-composites' microstructure and phase (EDX) , (XPS) were used to confirm the compositions of the powders. UV-Vis spectroscopy utilized to examine the particles' band gaps. Malachite green(MG) degradation was examined using the photocatalytic property of the nanocomposites, also the powders with 0.5 mol of Au exhibit the highest photocatalytic degradation efficiency. The reaction conditions for Au(0.5)/Fe3O4 were also evaluated.